REDESIGN BUCKET GUNA MENINGKATKAN KAPASITAS ANGKUT MESIN ELEVATOR PADA PROSES PENGERINGAN JAGUNG DRYER 3 DI PT. JJ - Putri Endah Suwarni; Samuel Arie Setiawan; Burhan Nudin; Andrie Oktivendra PI (Industrika : Jurnal Ilmiah Teknik Industri, 2022)
PT JJ is the largest and most integrated agri-food company in Indonesia. The company's main business units are the manufacture of animal feed, chicken breeding, poultry processing and agricultural cultivation. PT. JJ has 3 dryer machines, including dryer 1, dryer 2, and dryer 3, in this drying process there is a problem in dryer 3, where the carrying capacity of raw materials is not sufficient so that drying activities are hampered and the dryer machine does not work optimally, with problems This causes the production process to experience obstacles so that it wastes a lot of time which makes work ineffective and detrimental to the company. By doing this research, it aims to increase the carrying capacity of corn raw materials in the dryer machine which is only capable of transporting 17 tons/hour of raw material and to maximize the productivity of the dryer machine, so that production time is more effective and minimizes losses. After redesigning the bucket using the Common Formula Elevators formula, the bucket capacity/volume increased from 0.5 kg/bucket to 0.8 kg/bucket, increased the elevator engine capacity from 17 tons/hour to 23 tons/hour, and made changes in the form of a bucket elevator.